OPTIMALISASI PEMBELAJARAN BIOLOGI PADA SISWA TUNAGRAHITA MENGGUNAKAN MEDIA ALAT PERAGA PENGHANTARAN IMPULS - Nur Subkhi; Idah Hamidah; Bayu Pamungkas (Jurnal Biogenerasi, 2022)
Abstract Strategies and special treatment are needed in learning for mentally retarded students so make the learning process in class optimal. One of the special strategies to use is learning media. It is still rare for learning media for mentally retarded students and teachers rarely use media when learning biology. This study aims to determine: 1) An overview of optimizing biology learning in mentally retarded children, 2) An overview of the application of the impulses delivery aids media in learning biology in mentally retarded children. This type of research is qualitative with the library research method. Sources of data in this study are from literature or using library research which can be in the form of books, journals, proceedings and so on. The research instrument used is a checklist of document completeness. The data collection technique used is library research, by searching for relevant documents according to research needs, about mentally retarded students, effective learning media, effective learning, and teaching aids for mentally disabled children. From the research results obtained: 1) Optimization of learning biology in mentally retarded children by using the media for the delivery of implants, 2) The steps for implementing the media are: a) Students are formed into groups, b) Students are given a brief explanation / material, c) Each group is given one medium, d) Students are given directions / explanations for the use of the media, e) Students are instructed to arrange the media appropriately (according to the 3 types of implant delivery mechanism phases) within 15 minutes, f) Students are instructed to present the media of their work, and g) The teacher reflects (straightens) the student's percentage results. Keywords: Optimization, Learning Biology, Children with Intellectual Disabilities, Media Teaching Aids, Delivery of Implus Abstrak Diperlukan perlakuan khusus dalam pembelajaran pada siswa tunagrahita sehingga proses belajar di kelas menjadi optimal. Perlakuan khusus tersebut salah satunya dapat menggunakan media pembelajaran. Masih jarang media pembelajaran pada siswa tunagrahita dan Guru masih jarang menggunakan media saat pembelajaran biologi. Penelitian ini bertujuan untuk mengetahui: 1) Gambaran optimalisasi pembelajaran biologi pada anak tunagrahita, 2) Gambaran strategi penerapan media alat peraga penghantaran implus dalam pemebelajaran biologi pada anak tunagrahita. Jenis penelitian ini kualitatif dengan metode kepustakaan (library research). Sumber data dalam penelitian ini yaitu dari literatur yang jenisnya berupa buku, jurnal, prosiding, dan dokumen lain yang relevan dengan tujuan untuk mengumpulkan data sesuai kebutuhan penelitian. Instumen dalam penelitian yaitu menggunakan lembar (checklist) kelengkapan dokumen. Teknik pengumpulan data yang digunakan studi kepustakaan, yaitu dengan cara mencari dokumen yang relevan sesuai kebutuhan penelitian, yaitu tentang siswa tunagrahita, media pembelajaran yang efektif, pembelajaran yang efektif, dan media alat peraga pada anak tunagrahit. Dar hasil penelitian diperoleh: 1) Optimalisasi pembelajaran biologi pada anak tunagrahita, yaitu dengan menggunakan media alat peraga penghantaran implus, 2) Langkah-langkah penerapan media tersebut, yaitu: a) Siswa dibentuk menjadi beberapa kelompok, b) Siswa diberi penjelasan/ materi singkat, c) Setiap kelompok diberi satu media, d) Siswa diberi arahan/penjelasan penggunaan media, e) Siswa diinstruksikan menyusun media dengan tepat (sesuai 3 jenis fase mekanisme penghataran implus) dalam waktu 15 menit, f) siswa diinstruksikan mempresentasikan media hasil kerjanya, dan g) Guru memberi refleksi (meluruskan) hasil persentasi siswa. Kata Kunci: Optimalisasi, Pembelajaran Biologi, Siswa Tunagrahita, Media Alat Peraga, Penghantaran Implus